Aplicación de los ejes transversales en el proceso enseñanza-aprendizaje en el área de estudios sociales en el octavo noveno y décimo año de educación básica de la unidad educativa del milenio Lcda Olga Campoverde C del cantón Huaquillas, periodo lectivo 2012-2013 - Ortega Ruiz, Petra Piedad (2013)
Positive aspects as professional teachers who plan daily with a process of active, motivating, reflective and critical teaching guiding practices values ​​in low percentages, negative aspects as teachers that do not apply all keystones giving as results students with little practical value, ancentrales languages ​​and ignorance of the principles of good living.